Comparative study of the productivity of Madura Cattle and Its crossbreed with Limousin in Madura island - Farahdilla Kutsiyah; Kusmartono .; Trinil Susilawati (Jurnal Ilmu Ternak dan Veteriner, 2003)
Comparative study of the productivity between Madura cattle and crossbreed (Madura x Limousine) was done to identify problem and potential of crossbreed cattle at Madura island. Survey and direct field observation were conducted in Pamekasan. Data were descriptively analyzed or using correlation-regression, and t-test and indicated that service per conception (S/C) and calving rate (CR) of Madura cattle (n=34) and crossbreed (n=38) were 1.464 and 1.986; 58.8 and 52.6% respectively. Average birth weight (n = 17), weaning weight (n = 15) and ADG (average daily gain) pre weaning (n = 15) on calf of Madura cattle were 19.78 ± 1.224 kg; 119.53 ± 9.772 kg; 445 ± 48.53 g/day. Average birth weight (n = 17), weaning weight (n = 14) and ADG pre weaning (n = 14), on calf of crossbreed offspring were 27.60 ± 1.298 kg; 171.47 ± 31.055 kg; 678 ± 146.03 g/day. It is concluded that reproductive performance of Madura cattle was greater than their crossbreed, whereas production performance on calf of crossbreed offspring was greater than calf of Madura cattle. It is suggested that good quality and continuous supply of local feed must be maintained to prevent the negative effect for their growth. Key words: Madura cattle, Limousine cattle, crossbreed, productivity